Kesesuaian Penggunaan Alat Kontrasepsi Berdasarkan Permintaan KB pada Pasangan Usia Subur (PUS) di Kecamatan Puger Kabupaten Jember (Contraceptives Use Compatibility Based On Contraceptive Demand Among Fertile Age Couple at Puger Sub District, Jember Dist - Ririn Agustini; Dwi Martiana Wati; Andrei Ramani (Pustaka Kesehatan, 2015)
Fertile age couple in Indonesian and east java majority used contraceptives with pills and syringe method, while the purpose of family planning was limiting birth. Puger sub district is one of sub district in Jember district that fertile age couple also the most used contraceptives with pills and syringe method, while the purpose of family planning was limiting birth. This show that contraceptives use isn’t compatibility with contraceptive demand. The aim of this study was to analyze the contraceptives use compatibility based on demand contraceptive. A cross sectional study design was used in this study. This research involved 87 fertile age couple. This research was analyzed using chi-square with α=0,05. Age, parity, children of living, education level, health service place, cost of service had significant with contraceptive demand. Child of demand and income didn't have significant with contraceptive demand. Parity, children of living, health service place, cost of service had significant with contraceptives use compatibility. Age, child of demand, eduction dan income didn't have significant with contraceptives use compatibility Contraceptive demand were also had a significant correlation with use compatibility. Keywords: contraceptives use compatibility, contraceptives demand